Improving Business Performance Results Through Evaluating Business Information Needs in Makassar City Culinary Industry Businesses - Halim, Sri Endarti (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2023)
One of the keys to success in running a culinary business is the ability to make the right decisions based on accurate and relevant information. Evaluation of business information needs also needs to pay attention to unique factors that affect business performance, such as the need for innovation in menus, understanding of local flavours, and the need for a deep understanding of food and lifestyle trends.This research aims to examine how the evaluation of business information needs in Makassar City culinary industry businesses is a crucial step in an effort to improve business performance results and strengthen the contribution of the culinary sector to the local economy.The research method in this research uses qualitative descriptive to describe a business performance result that comes from aspects of the ability to process and evaluate business information. The data collection technique used in this study was to use a questionnaire distributed to 23 number of psang epe culinary business businesses at Anjungan Pantai Losari Makassar City. The results of this study provide the importance of evaluating business information needs and a better understanding of business information in improving the performance and success of banana epe culinary businesses in Makassar City.